Development of Seed Extracting Machine for Brinjal - Joshi, D C; Sutar, R F; Vyas, D K (Journal of Agricultural Engineering, 2005)
A mechanical brinjal seed extractor was developed. The test results observed that at higher rotational speed, the recovery was higher and at lower speed seed recovery was lower. The average dimensions of the brinjal fruit i.e. the length, diameter (min) & diameter (max) were 122.27, 26.0 and 38.9 mm respectively. The bulk density of the brinjal was 378 kg/mÂ³. The seed extraction capacity by machine and manual seed extraction is 206.25 and 15.05 kg/hr respectively. The seed extraction cost by mechanical seed extraction is 5 times less that of manual seed extraction. If the machine is operated for 8 hr per day, cost of the machine is recovered in only 17 days of operation.